Anthology of Arabic Discourse on Translation - Shamma, Tarek; Salama-Carr, Myriam (Translation Studies in Translation, 2022)
"This anthologybrings the keywritings on translation in Arabic in the pre-modern era, extending from the earliest times (sixth century CE) until the end of World War I, to a global English-speaking audience. The texts are arranged chronologically and organized by two historical periods: the Classical Period, and the Nahda Period. Each text is preceded by an introduction about the selected text and author, placing the work in context, and discussing its significance. The texts are complemented with a theoretical commentary, discussing the significance for the contemporary period and modern theory. A general introduction covers the historical context, main trends, research interests, and main findings and conclusions. The two appendices provide statistical data of the corpus on which the anthology is based, more than 500 texts of varying lengths extending throughout the entire period of study. This collection contributes to the development of a more inclusive and global history of translation and interpreting. Translated, edited, and analyzed by leading scholars, this anthology is an invaluable resource for researchers, students, and translators interested in translation studies, Arab/Islamic history, and Arabic language and literature, as well as Islamic theology, linguistics, and the history of science."